Correction: Plyasova et al. Penetration into Cancer Cells via Clathrin-Dependent Mechanism Allows L-Asparaginase from Rhodospirillum rubrum to Inhibit Telomerase. Pharmaceuticals 2020, 13, 286 - Anna A. Plyasova; Marina V. Pokrovskaya; Olga M. Lisitsyna; Vadim S. Pokrovsky; Svetlana S. Alexandrova; Abdullah Hilal; Nikolay N. Sokolov; Dmitry D. Zhdanov (MDPI AG, 2024)
In the original publication [...]